2021
DOI: 10.1007/s12011-021-02611-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Zinc Level and Pre-eclampsia Risk in African Women: a Systematic Review and Meta-analysis

Abstract: Some studies have reported the association between maternal serum zinc (Zn) levels and pre-eclampsia. However, many studies have reported controversial results. Hence, this systematic review and meta-analysis was planned to generate summarized evidence on the association between maternal serum Zn levels and pre-eclampsia in African women. Four electronic databases such as PubMed, Hinari, Google Scholar, and African Journals Online were searched for studies published in English. Joanna Briggs Institute Meta-Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…Women with pre-eclampsia had lower zinc concentrations compared to healthy pregnant controls (SMD -0.587, 95%CI: -0.963 to -0.212, 1091 participants, 14 studies, I 2 88%), measured largely in the third trimester (36). Significantly lower zinc concentrations among pre-eclamptic women compared to healthy controls were only found in Asia (36,74,75) and sub-Saharan Africa (76), not in other regions of the world.…”
Section: Definite Associationsmentioning
confidence: 94%
“…Women with pre-eclampsia had lower zinc concentrations compared to healthy pregnant controls (SMD -0.587, 95%CI: -0.963 to -0.212, 1091 participants, 14 studies, I 2 88%), measured largely in the third trimester (36). Significantly lower zinc concentrations among pre-eclamptic women compared to healthy controls were only found in Asia (36,74,75) and sub-Saharan Africa (76), not in other regions of the world.…”
Section: Definite Associationsmentioning
confidence: 94%
“…Several studies have found significantly lower level of serum zinc in preeclampsia patients compared with pregnancies without preeclampsia. 6 In this study, the average zinc levels of PE patients were 43.90 ± 15.79 mcg/dL (15-86 mcg/ dL), significantly lower than patients without preeclampsia which was 48.77 ± 10.54 mcg/dL (22-83 mcg/dL).…”
Section: Characteristicmentioning
confidence: 51%
“…Research on Indians found that serum zinc levels in mild and severe preeclampsia women were lower at 12.72 μmol/L in mild preeclampsia and 12.04 μmol/L in severe preeclampsia compared with 15.64 μmol/L in normal pregnancy. [5][6][7][8] Research related with the benefits of zinc in preeclampsia had not been conducted in Indonesia, especially in dr. Mohammad Hoesin General Hospital Palembang. Because of that, authors are interested in proving the relationship between zinc and preeclampsia in the pregnant women population at dr. Mohammad Hoesin General Hospital Palembang.…”
Section: Introductionmentioning
confidence: 99%
“…13 Zinc plays a function in placental morphogenesis and the regulation of maternal blood pressure during pregnancy, which means that a zinc deficit impairs fetal growth and results in blood pressure problems. 14 In addition, low serum Zn levels lead to oxidative stress and lower superoxide dismutase activity, both of which increase blood pressure due to increased Zn transfer from the mother to the developing fetus, low Zn levels, and higher urine Zn excretion in preeclampsia females. On the other hand, preeclampsia's enhanced lipid peroxidation lowers the amounts of transporter proteins and estrogens, which lowers serum Zn levels.…”
Section: Discussionmentioning
confidence: 99%